Non-Steroidal Anti-Inflammatory Drugs Consumption and Awareness About Risks During Pregnancy In AL-Bayda City, Libya - Asma Omar; Hajer Omar; Anwar Mohamad; Salhah Haroon (AlQalam Journal of Medical and Applied Sciences, 2025)
Non-steroidal anti-inflammatory drugs are one of the most common prescribed medications for relieving pain, fever, and inflammation. Most NSAIDs are available without a prescription, and they often consumed by pregnant women for short periods of time to treat mild pain. However, these drugs can cause substantial teratogenic effects. NSAIDs such as aspirin, diclofenac sodium and ibuprofen might cause oligohydramnios (low amniotic fluid) or prenatal renal abnormalities if taken in the late second half of pregnancy. The US Food and Drug Administration (FDA) announced that taking NSAIDs in the period from the fifth month of pregnancy to delivery is not safe. This research was conducted to explore pregnant women’s knowledge about NSAIDs during gestation period as well as consumption patterns. This study was conducted during the period from 10/2/2022 to 10/3/2022 in private clinics in Al-Bayda, Al-Quba cities as well as Al -Thawra hospital targeting 250 pregnant women who asked gently to fill in a printed questionnaire. The questionnaire has a variety of questions regarding age, consumption of NSAIDs during pregnancy and awareness about the benefits and risks of these drugs. Our study indicated that 55.6% of the pregnant women were in the range of twenty-two to twenty-nine years old. Half of pregnant women (50%) did consume painkillers (NSAIDs). Aspirin was the most common drug (55%). Forty-five out of 125 were consuming these drugs without prescription (36%). The common reason for consuming NSAIDs was varicose veins (31%). 30.4% of pregnant women had a miscarriage. Poor fetal growth was the most common cause of miscarriage among 29% of participants. Sixty-five percent of the participants knew that using this kind of drugs in the last month of pregnancy affect their health negatively. Only 4% of them had miscarriage due to consumption of NSAIDs. Pain management noticed in 90% of pregnant women. Awareness about the positive and negative effects of NSAIDs was noticed in 55% of the participants. In conclusion, despite the fact which is consumption of NSAIDs throughout pregnancy has undesirable effects on pregnant women and fetus, these drugs are widely prescribed by doctors to pregnant women. NSAIDs should not be prescribed during pregnancy unless mother’s outcomes exceed the possible fetal adverse effects. Our research found no significant relation between NSAIDs consumption in the period of pregnancy and miscarriage. Although our results were satisfied, concentrated education programs are needed to spread knowledge in our society and another research must be conducted on a large sample size to investigate the differences among this study with the current research. تعتبر مضادات الالتهاب غير الستيرويدية من أكثر الأدوية الموصوفة شيوعًا لتخفيف الألم والحمى والالتهاب. معظم مضادات الالتهاب غير الستيرويدية متاحة بدون وصفة طبية، وغالبًا ما تستهلكها النساء الحوامل لفترات قصيرة من الوقت لعلاج الألم الخفيف. ومع ذلك، يمكن لهذه الأدوية أن تسبب تأثيرات جانبية كبيرة. مضادات الالتهاب غير الستيرويدية مثل الأسبرين وديكلوفيناك الصوديوم والإيبوبروفين قد تسبب قلة السائل الأمنيوسي (انخفاض السائل الأمنيوسي) أو تشوهات الكلى قبل الولادة إذا تم تناولها في أواخر النصف الثاني من الحمل. أعلنت إدارة الغذاء والدواء الأمريكية أنه لا ينصح بتناول مضادات الالتهاب غير الستيرويدية في الفترة من الشهر الخامس من الحمل وحتى الولادة. تم إجراء هذا البحث لاستكشاف معرفة النساء الحوامل حول مضادات الالتهاب غير الستيرويدية أثناء فترة الحمل بالإضافة إلى أنماط الاستهلاك. أجريت هذه الدراسة خلال الفترة من 2022/10/2 إلى 2022/3/10 في العيادات الخاصة في مدينة البيضاء والقبة وكذلك مستشفى الثورة واستهدفت 250 امرأة حامل حيث طلبنا منهن ملء استبيان مطبوع. يحتوي الاستبيان على مجموعة متنوعة من الأسئلة المتعلقة بالعمر واستهلاك مضادات الالتهاب غير الستيرويدية أثناء الحمل والوعي بفوائد ومخاطر هذه الأدوية. أشارت دراستنا إلى أن 55.6% من النساء الحوامل تتراوح أعمارهن بين 22_29 سنة. نصف النساء الحوامل (50٪) يتناولن مسكنات الألم (مضادات الالتهاب غير الستيرويدية). وكان الأسبرين هو الدواء الأكثر شيوعاً (55%). وكان 45 من أصل 125 يتناولون هذه الأدوية دون وصفة طبية (36%). وكان السبب الشائع لتناول مضادات الالتهاب غير الستيرويدية هو الدوالي (31٪). 30.4% من النساء الحوامل تعرضن للإجهاض. كان ضعف نمو الجنين هو السبب الأكثر شيوعًا للإجهاض بين 29٪ من المشاركات. 65% من المشاركات كن يعرفن أن استخدام هذا النوع من الأدوية في الشهر الأخير من الحمل يؤثر على صحتهن سلباً. فقط 4% منهن تعرضن للإجهاض بسبب تناول مضادات الالتهاب غير الستيرويدية. لوحظت إدارة الألم لدى 90٪ من النساء الحوامل. ولوحظ الوعي بالآثار الإيجابية والسلبية لمضادات الالتهاب غير الستيرويدية لدى 55% من المشاركات في الختام، على الرغم من أن تناول مضادات الالتهاب غير الستيرويدية طوال فترة الحمل له آثار غير مرغوب فيها على النساء الحوامل والجنين، إلا أن هذه الأدوية توصف على نطاق واسع للنساء الحوامل. لا ينبغي وصف مضادات الالتهاب غير الستيرويدية أثناء الحمل إلا إذا تجاوزت نتائج الأم التأثيرات الضارة المحتملة على الجنين. لم يجد بحثنا أي علاقة ذات دلالة إحصائية بين استهلاك مضادات الالتهاب غير الستيرويدية في فترة الحمل والإجهاض. وعلى الرغم من أن نتائجنا كانت مرضية، إلا أن هناك حاجة إلى برامج تعليمية مركزة لنشر المعرفة في مجتمعنا ويجب اجراء بحث آخر على عينة كبيرة الحجم لمعرفة الاختلافات بين هذه الدراسة مع البحث الحالي